2019
DOI: 10.1177/0003489419898711
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Unilateral Cordotomy on Perception of Dysphagia

Abstract: Objectives: CO2 laser medial transverse cordotomy is a permanent static procedure performed to achieve adequate functional airway in cases of posterior glottic stenosis and bilateral vocal fold paralysis. Although it is the preferred method to manage long-term bilateral vocal fold immobility, it is widely believed that cordotomy has the potential to cause aspiration. The minimal existing data on the effect surgical enlargement of the glottic airway on swallowing function is heterogeneous. Through investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…As previously reported, this type of surgical procedure does not require prophylactic tracheotomy, thereby minimizing post-operative morbidity and hospitalization time and improving vocal outcomes [ 27 , 28 ]. Our data, in line with that reported in the literature [ 29 , 30 ], show that CO 2 laser PC ± MPA does not negatively affect swallowing function, although it does cause wide unilateral posterior glottic incompetence, as this is the aim of the surgical procedure itself. A number of different scales (i.e.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As previously reported, this type of surgical procedure does not require prophylactic tracheotomy, thereby minimizing post-operative morbidity and hospitalization time and improving vocal outcomes [ 27 , 28 ]. Our data, in line with that reported in the literature [ 29 , 30 ], show that CO 2 laser PC ± MPA does not negatively affect swallowing function, although it does cause wide unilateral posterior glottic incompetence, as this is the aim of the surgical procedure itself. A number of different scales (i.e.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, is evident that laryngeal sphincteric function is the result of a more complex physiologic mechanism, wherein glottic closure by TA muscles contraction is only a part of the entire process. Consequently, if the approximation of false vocal folds and arytenoids to epiglottic petiole is restored, airway protection may still be guaranteed [ 29 ]. However, to ensure maintenance of sphincteric mechanisms, it is of crucial importance to preserve at least the postero-lateral part of the arytenoid to allow the anatomical integrity of the hypopharyngo-laryngeal wall, thereby minimizing the risk of swallowing disorders [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there were no major complications and no revision procedures or tracheotomies were required 8 . With regard to dysphagia, a recent study by Conklin et al found no statistically significant differences in Eating Assessment Tool‐10 scores pre‐ and postoperatively in 15 patients undergoing unilateral CO 2 laser cordotomy 9 …”
Section: Discussionmentioning
confidence: 96%
“…7 The use of static ablative procedures such as posterior cordotomy has long been thought to improve airway caliber at the expense of phonation and, in some cases, deglutition. 8 Unilateral cordotomy has been demonstrated to successfully improve respiratory function and alleviate obstruction at the level of the glottis. 8 However, there are reports of long-term tracheostomy dependence and the need for revision ablative procedures including arytenoidectomy and contralateral cordotomy.…”
Section: Introductionmentioning
confidence: 99%
“…8 Unilateral cordotomy has been demonstrated to successfully improve respiratory function and alleviate obstruction at the level of the glottis. 8 However, there are reports of long-term tracheostomy dependence and the need for revision ablative procedures including arytenoidectomy and contralateral cordotomy. Given the rarity of BVFI, most reports regarding unilateral cordotomy are single-institution studies with limited sample sizes.…”
Section: Introductionmentioning
confidence: 99%